2016
DOI: 10.1093/ntr/ntw152
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Exposure and Low Blood Lead Levels in Association With Attention-Deficit Hyperactivity Disorder and Its Symptom Domain in Children: A Community-Based Case–Control Study

Abstract: Aim:Secondhand smoke (SHS) is a major indoor pollutant. We examined the possible association between exposure to both SHS and low levels of lead and attention-deficit–hyperactivity disorder (ADHD) and its symptom domain in children.Methods:This case–control study was based on the results of a community survey using the ADHD rating scale conducted in 49 elementary schools. Both cases and control subjects were confirmed by a child psychiatrist. Each case was matched with one control subject according to gender, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…The concentrations of urinary cotinine in Los Angeles and Beijing in this study were in the same magnitude of other nonsmoking population studies from 20 countries (Table S4) (20,(33)(34)(35)(36). Thus, the level of urinary cotinine in Los Angeles (LA-before + LA-after) was at lower levels compared with that in studies from other countries (Table S4) (20).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The concentrations of urinary cotinine in Los Angeles and Beijing in this study were in the same magnitude of other nonsmoking population studies from 20 countries (Table S4) (20,(33)(34)(35)(36). Thus, the level of urinary cotinine in Los Angeles (LA-before + LA-after) was at lower levels compared with that in studies from other countries (Table S4) (20).…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, urinary cotinine in Beijing was at a relatively higher levels, and it was comparable with levels in studies from Korea and several Europe countries (e.g. Portugal and Hungry) (20,35) but markedly lower that the levels in an Italian Study (36). It is likely that the higher urinary cotinine concentration observed in Beijing was due to a higher prevalence of smoking (30.2%) (37) as compared with Los Angeles (14.3%) (38), together with the markedly higher population density in Beijing (4,700 persons km − 2 ) as compared to that in Los Angeles (2,300 persons km − 2 ) (39).…”
Section: Discussionsupporting
confidence: 77%
“…Fourth, Gard et al 53 reported that girls prenatally exposed to nicotine had greater hyperactivity and/or impulsivity symptoms. Joo et al 54 also found that prenatal secondhand smoke exposure increased the risk of ADHD, especially in terms of hyperactivity and/or impulsivity. It seems that prenatal smoking and/or nicotine exposure may be more relevant to the hyperactivity components of ADHD.…”
Section: Figurementioning
confidence: 96%
“…The cigarette smoke data were composed of 21 studies that included a total of 58 sampling events with measurements of prenatal exposures to smoke determined by maternal survey data [16,[75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94]. Four of these studies included exposure data that were specific to the first trimester and included 14 sampling events [80,84,88,94].…”
Section: Cigarette Smokementioning
confidence: 99%